The Role of Servant Leadership on Sustainable Marketing: An Analytical Study on the Perspective A Sample of Employees in Private Sector Education in the Raparin Independent Administration - Faisal Saeed, Rezhiar; Othman, Bestoon (JBS Nexus, 2026)
Under the Raparin Independent Administration, this study explored how servant leadership might support sustainable marketing strategies in the private school industry. Emphasizing the servant leadership facets of compassion, emotional healing, empowerment, and community service, this study investigates how these elements impact sustainable marketing campaigns from the viewpoint of staff members. Data were gathered from a sample of 237 employees of private educational institutions using a quantitative methodology. To examine the connections between servant leadership traits and sustainable marketing results, clever PLS (Partial Least Squares) structural equation modeling was used. The findings show that altruism and empowerment are the most important aspects of servant leadership that greatly improve sustainable marketing strategies. It was also shown that community services and emotional healing have a significant impact on developing a sustainable culture in businesses. To match marketing tactics to the objectives of environmental, social, and economic sustainability, this study emphasizes the significance of servant leadership. These findings highlight the need to develop servant leadership traits to support sustainable marketing initiatives and offer insightful information to leaders and policymakers in the education sector. By showing how servant leadership can be used practically to achieve long-term sustainability in marketing strategies, this study adds to the body of literature.